Educação financeira e aplicação em renda fixa - GONÇALVES, Beatriz Nunes (2023)
One of the main objectives is to present the most relevant types of investments focused on fixed income. This study is based on bibliographical research in order to inform potential investors about financial education and their investment methods, showing that not every enterprise is the same, as each application obtains different returns and risks. In this way, it was presented from the structure of the theoretical foundation covering the history of money in the country, the subjects of financial education and financial mathematics and how they are somehow interconnected. In addition to commenting on the risk and return of an investment, emphasizing the Discounted Cash Flow (DCF), considering that it assumes that each investment generates a cash flow during a certain time. Emphasizing that in addition to the FCD, it is necessary to make some calculations regarding profitability and risk indicators. The latter being described only on the Internal Rate of Return (IRR).